2008
DOI: 10.1016/j.jmb.2008.08.049
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Catalytic Mechanism of Human sEH Phosphatase by Site-Directed Mutagenesis and LC–MS/MS Analysis

Abstract: The bifunctional human soluble epoxide hydrolase (sEH) is implicated as a regulator of diverse physiological processes due to the brakedown of arachidonic acid derived signalling molecules like epoxyeicosatrienoic acids (EETs) by its epoxide hydrolase domain. Recently, we discovered that the sEH N‐terminal domain displays a novel phosphatase activity. sEH accepts the generic substrate 4‐NPP as well as lipid phosphates, but the physiological role remains uncertain. The phosphatase domain contains three conserve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…Alignment of these (Fig. 1A) showed that they had one or more conserved motifs typical of phosphatases including; 1) an aspartic acid residue as the catalytic nucleophile, 2) a serine or threonine for binding the phosphate group, and, 3) two aspartic acid residues thought to be important for Mg 2+ binding [7, 11]. Two phosphatases (Phos17294 and Phos10352) were eliminated from further analysis because they lacked the second serine or threonine conserved motif.…”
Section: Resultsmentioning
confidence: 99%
“…Alignment of these (Fig. 1A) showed that they had one or more conserved motifs typical of phosphatases including; 1) an aspartic acid residue as the catalytic nucleophile, 2) a serine or threonine for binding the phosphate group, and, 3) two aspartic acid residues thought to be important for Mg 2+ binding [7, 11]. Two phosphatases (Phos17294 and Phos10352) were eliminated from further analysis because they lacked the second serine or threonine conserved motif.…”
Section: Resultsmentioning
confidence: 99%
“…To demonstrate covalent catalysis in the H18D variant, we first sought to obtain direct evidence for the formation of a phospho-enzyme intermediate. Using a 32 P-labeled phosphate group 26,49 in the Glc1P substrate, we could clearly show the incorporation of radiolabel into the wildtype enzyme, but did not observe the same for the H18D variant (Figure S2). The H18A variant did not incorporate radiolabel, as expected from the requirement of an enzyme nucleophile to form a phosphorylated enzyme.…”
Section: Resultsmentioning
confidence: 90%
“…49,50 We therefore applied chemical reduction with sodium borohydride to convert aspartylphosphate into the non-labile homoserine (Figure S3a) and analyzed the enzyme by tryptic peptide mass fingerprinting. 49 For HAD13 incubated with Glc1P, indeed, the expected peptide containing the catalytic nucleophile Asp9 present as homoserine was found in high abundance (Figure S3 and Table S3). The same peptide was not detectable for the control (HAD13 incubated in absence of Glc1P, Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it is proposed that the hydrolase domain of sEH regulates the activity of sEH-P 30 and vice versa. Thus, it was important to develop an assay system with an isolated N-terminal sEH-P domain to exclude the influence of the C-terminal domain.…”
Section: Resultsmentioning
confidence: 99%
“…3,4 The sEH-P has structural and sequential similarity to the haloacid dehalogenase family and cleaves phosphate esters in a magnesium-dependent nucleophilic attack by Asp9. 5 Endogenic substrates of sEH-P are isoprenoid phosphates 6 and lysophosphatidic acids. 7,8 Phenotypic differences between mice treated with sEH-H inhibitors and sEH knockout mice, which lack both domains, indicate a role of sEH-P in hypercholesterolemia 9 and pulmonary hypertension.…”
Section: Introductionmentioning
confidence: 99%